Perancangan Ulang Tampilan Elemen “Liquid Glass” pada iOS 26 dengan Metode Design Thinking - I Wayan Brahmani Novus Abasan; I Gede Santi Astawa (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
As a pioneer in mobile interface design, Apple introduced a unique and elegant element called “Liquid Glass”. Although this element is considered aesthetically attractive, many users and developers complain about usability and text readability issues. This study offers a solution by redesigning “Liquid Glass” to achieve high usability and readability. Using the Design Thinking method, this study identified the main problems users face in using this element. From a survey of 15 iOS users, this redesign scored 81 (grade B) on the System Usability method.